(untitled) (Proceedings of the International Conference on Food, Nutrition, Health and Lifestyle, 2025)
Diabetes, neurodegenerative diseases and cancer are some of the major public health issues worldwide. Various synthetic drugs are available for the treatment of these diseases, however, most of them exhibit side-effects. Despite their availability, most of these drugs are unaffordable for a particular sect of population. Also, most of the commercial drugs exhibit critical effects upon long term consumption and sometimes can also be lethal. Flavonoids are bioactive polyphenols that has potent pharmacological properties. In the recent times, apigenin, quercetin and naringenin, derived from citrus plants, are used extensively in the treatment of various diseases and being herbal in nature, these compounds are reported to show no significant side-effects. These said dietary flavonoids do possess high antioxidant, anti-inflammatory, anti-hyperglycemic and anti-apoptotic properties. This review summarises the adverse effects of synthetic drugs available for treatment, suggesting the efficacy of the mentioned flavonoids as possible alternative medicinal approach against the usage of the commercial drugs. In experimental researches like cell culture and animal models, these dietary flavonoids can be used alternatively towards treating those diseases, considering their positive effects. However, further clinical trials are required on humans to check for toxicity.